Reading comprehension and its relationship with the levels of communicative competence - Misari, Alexis (2023)
There is research whose results show a low or moderate level of communicative competence in the Peruvian population, which is why we seek to know if it is possible to strengthen the level of communicative competence through the development of reading comprehension. Therefore, the purpose of the research is to determine how reading comprehension affects communicative competence; likewise, to determine the correlation between the dimensions of reading comprehension (literal, inferential and critical) and communicative competence. Methodologically, the study design is descriptive-correlational. The sample is made up of 31 students in the fourth grade of secondary school at IE No. 1190 in Lurigancho-Chosica. In addition, a questionnaire and a test were applied for data collection. Finally, the results show that reading comprehension has a significant impact on communicative competence (p < 0.05; Rho = 0.746).